Credit card debt management: a profile study of young professionals / Rashidah Ahmad and Normah Omar - Ahmad, Rashidah; Omar, Normah (Universiti Teknologi MARA Cawangan Selangor, 2013)
As at 30th June 2012, the total amount of credit cards outstanding bills stood at RM 29.9 billion. The 2010 statistics issued by the Department of Solvency Malaysia, showed a worrying trend of young Malaysians who were below the age of 30 being declared bankrupt due to credit card debts. Some 209 or 46.04% out of a total of 454 Malaysians who were declared bankrupt in 2010 are among those aged “30 years and below. This study distributed questionnaire to participants of “debt-ridden” young professionals in managing their financial situation under the Central Bank of Malaysia. The aim of this study is to explore the demographic profiles of these respondents, to identify spending habits as well as to examine participants’ affordability to pay their credit card bills. This study also hopes to explore viable strategies to curb the respondents’ dependence and possible misuse of their credit cards for their day-to-day transactions. The findings implicate some very challenging trends. First, the increasing use of credit cards on entertainment and online shopping among young professionals. Secondly, is the respondents’ inclination to make “minimum payments” on their outstanding credit card bills. Thirdly, many respondents “own” more than three credit cards during the data collection period. The fourth finding highlights the “trend” that respondents owe high amount of outstanding accumulated credit card debts when the due date expires. Finally, it is also observed that the respondents have the habit of borrowing from others. Onsite observations further implicate that some of these participants desperately need help to kick out their habit of credit card dependence and misuse. Furthermore, some of these young professionals are not even aware of the negative impact of possible insolvency and bankruptcy status on their future undertakings.